The ruthenium isotopic composition of the oceanic mantle - Bermingham, K.R. (Earth Planet Sci Lett, 2017)
The approximately chondritic relative, and comparatively high absolute m antle abundances of the highly siderophile elem ents (HSE), suggest that their concentrations in the bulk silicate Earth were primarily established during a final ~0.5 to 1% of “late accretion” to the mantle, following the cessation of core segregation. Consequently, the isotopic composition of the HSE Ru in the mantle reflects an amalgamation of the isotopic compositions of late accretionary contributions to the silicate portion of the Earth. Among cosm ochem ical materials, Ru is characterized by considerable mass-independent isotopic variability, making it a powerful genetic tracer of Earth’s late accretionary building blocks. To define the Ru isotopic composition of the oceanic mantle, the largest portion of the accessible mantle, we report Ru isotopic data for materials from one Archean and seven Phanerozoic oceanic m antle domains. A sample from a continental lithospheric mantle domain is also examined. All samples have identical Ru isotopic compositions, within analytical uncertainties, indicating that Ru isotopes are well mixed in the oceanic mantle, defining a μ(100)Ru value of 1.2 ± 7.2 (2SD). The only known meteorites with the same Ru isotopic composition are enstatite chondrites and, when corrected for the effects of cosmic ray exposure, mem bers of the Main Group and sLL subgroup of the lAB iron meteorite complex which have a collective CRE corrected μ(100)Ru value of 0.9 ± 3.0. This suggests that materials from the region(s) of the solar nebula sampled by these m eteorites likely contributed the dominant portion of late accreted materials to Earth’s mantle.